Inflammatory biomarkers, disease activity and spinal disease measures in patients with ankylosing spondylitis after treatment with infliximab. Issue 4 (20th July 2007) - Visvanathan, S; Wagner, C; Marini, J C; Baker, D; Gathany, T; Han, J; van der Heijde, D; Braun, J
Abstract : Objective: To evaluate the relationship between biomarker levels and disease activity and the spinal inflammation detected by magnetic resonance imaging (MRI) in patients with ankylosing spondylitis (AS). Methods: Patients with AS were randomly assigned in a 3:8 ratio to receive infusions of placebo or 5 mg/kg infliximab at weeks 0, 2, 6, 12 and 18. Sera were collected for biomarker analysis at weeks 0, 2 and 24 and were analysed for levels of interleukin-6 (IL-6), vascular endothelial growth factor (VEGF) and C-reactive protein (CRP). Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) scores and pre- and post-gadolinium T1 and short τ inversion recovery MRIs were collected at baseline and week 24. Results: Significantly greater reductions in IL-6, VEGF and CRP were observed at weeks 2 and 24 in the infliximab group compared with the placebo group (all p<0.001). Baseline IL-6 levels >7.38 pg/ml and CRP levels >1.5 mg/dl were associated with increased rates of clinical response after 24 weeks. Multiple regression analyses showed that reductions from baseline to week 2 in IL-6, but not CRP or VEGF, were significantly associated with reductions in MRI activity and BASDAI scores from baseline to week 24 in the infliximab group (p<0.001). Conclusions: Significant reductions in IL-6, VEGF and CRP were observed with infliximab compared with placebo. High levels of baseline IL-6 and CRP were associated with clinical response after infliximab treatment. Early reductions in IL-6 were significantly associated with improvements in disease activity and the spinal inflammation detected by MRI.